2021
DOI: 10.3389/fimmu.2021.748325
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Innate Immunity in Visceral Leishmaniasis and Their Implication in Vaccine Development

Abstract: Leishmaniasis is endemic to the tropical and subtropical regions of the world and is transmitted by the bite of an infected sand fly. The multifaceted interactions between Leishmania, the host innate immune cells, and the adaptive immunity determine the severity of pathogenesis and disease development. Leishmania parasites establish a chronic infection by subversion and attenuation of the microbicidal functions of phagocytic innate immune cells such as neutrophils, macrophages and dendritic cells (DCs). Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 215 publications
(272 reference statements)
0
49
0
Order By: Relevance
“…When investigating vaccine vehicles or surrogate pathogens as antigens, it is therefore crucial to determine the response of DCs, which then orchestrate the successive phases of the immune reaction. Our results demonstrate that L. tarentolae is actually engulfed by monocyte-derived DCs, similarly to human and canine parasitic leishmaniae (e.g., [ 30 ]). However, while DC maturation is normally impaired by pathogenic leishmaniae (reviewed in [ 19 ]), we observed that L. tarentolae infection induces a proper activation of these cells, consistent with an increase in the expression of molecules involved in antigen presentation (HLA-DR II and CD83 expression) and CD4+ T cell stimulation (CD80 expression).…”
Section: Discussionmentioning
confidence: 54%
“…When investigating vaccine vehicles or surrogate pathogens as antigens, it is therefore crucial to determine the response of DCs, which then orchestrate the successive phases of the immune reaction. Our results demonstrate that L. tarentolae is actually engulfed by monocyte-derived DCs, similarly to human and canine parasitic leishmaniae (e.g., [ 30 ]). However, while DC maturation is normally impaired by pathogenic leishmaniae (reviewed in [ 19 ]), we observed that L. tarentolae infection induces a proper activation of these cells, consistent with an increase in the expression of molecules involved in antigen presentation (HLA-DR II and CD83 expression) and CD4+ T cell stimulation (CD80 expression).…”
Section: Discussionmentioning
confidence: 54%
“…Each subset can display different functions: broadly, classical monocytes exhibit strong phagocytosis abilities; intermediate monocytes are characterised by their abilities to induce T cell stimulation and high ROS production, as well as pro-angiogenic abilities; and non-classical monocytes are characterised by their patrolling behaviour of the vascular endothelium [ 20 ]. Importantly, the role of these different subsets in VL patients is poorly characterised [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each subset can display different functions: broadly, classical monocytes exhibit strong phagocytosis abilities; intermediate monocytes are characterised by their abilities to induce T cell stimulation and high ROS production, as well as pro-angiogenic abilities; and non-classical monocytes are characterised by their patrolling behaviour of the vascular endothelium[20]. Importantly, the role of these different subsets in VL patients is poorly characterised[21].Here we tested whether the different monocyte subsets isolated from VL patients express PDL-1, and if so, if they express it differentially. Results presented inFig 2 and S1 Table show that directly ex vivo, monocytes in the PBMCs of VL patients express PDL1.…”
mentioning
confidence: 99%
“…Nevertheless, neutrophil-mediated protective immunity has been previously demonstrated in other vaccination regimens including modified vaccinia Ankara virus, poxvirus and live attenuated tuberculosis vaccine. 79 Recent evidence shows that human neutrophils can be polarized in vitro to an N1 or N2 phenotype, similar to polarization phenotypes described for macrophages. 80 Polarization of neutrophils to N1 was done under normoxia and in the presence of LPS, IFN-γ and IFN-β, whereas N2 polarized neutrophils were done under hypoxic F I G U R E 2 Overview of the heterogeneity of neutrophil subpopulations and its functional implications to Leishmania infection.…”
Section: Neutrophil Subpopulations: Ldgs Neutrophils With Antigen Pre...mentioning
confidence: 60%
“…Moreover, these results suggest that phagocytosis is associated with a transcriptional programme devoted to antigen presentation, which is intriguing considering evidence that phagocytosis accelerates neutrophil apoptosis in vivo. Nevertheless, neutrophil‐mediated protective immunity has been previously demonstrated in other vaccination regimens including modified vaccinia Ankara virus, poxvirus and live attenuated tuberculosis vaccine 79 …”
Section: Neutrophil Subpopulations: Ldgs Neutrophils With Antigen Pre...mentioning
confidence: 99%